2015
DOI: 10.1007/s00401-015-1516-y
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Aß pathology: hypotheses, discoveries, and yet unresolved questions from experimental and human brain studies

Abstract: In brains of patients with Alzheimer's disease (AD), Aβ peptides accumulate in parenchyma and, almost invariably, also in the vascular walls. Although Aβ aggregation is, by definition, present in AD, its impact is only incompletely understood. It occurs in a stereotypical spatiotemporal distribution within neuronal networks in the course of the disease. This suggests a role for synaptic connections in propagating Aβ pathology, and possibly of axonal transport in an antero- or retrograde way-although, there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 136 publications
1
67
0
3
Order By: Relevance
“…In contrast with α-synuclein, tau pathology in Alzheimer's disease (AD) predominantly spreads in the anterograde direction as seen in the dentate gyrus, even if experimental studies demonstrated the possibility of either anterograde or retrograde spread [2,4]. As pointed out by Lewis and Dickson in this issue [4], it is not yet clear whether such anterograde spread is shared with other tau-related diseases such as progressive supranuclear palsy, corticobasal degeneration, or Pick´s disease.…”
Section: Similarities and Differences In Pathological And Experimentamentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast with α-synuclein, tau pathology in Alzheimer's disease (AD) predominantly spreads in the anterograde direction as seen in the dentate gyrus, even if experimental studies demonstrated the possibility of either anterograde or retrograde spread [2,4]. As pointed out by Lewis and Dickson in this issue [4], it is not yet clear whether such anterograde spread is shared with other tau-related diseases such as progressive supranuclear palsy, corticobasal degeneration, or Pick´s disease.…”
Section: Similarities and Differences In Pathological And Experimentamentioning
confidence: 99%
“…Even though hierarchical distribution as formulated by Thal and CERAD staging are current frameworks for Aβ spread [2], their underlying mechanisms are poorly explained. As described in the review by Eisele and Duyckaerts in this issue [2], experimental studies have provided compelling evidence that brain inoculations of "seeds" of aggregated Aβ can induce the further aggregation of endogenous Aβ, which is mechanistically much more straightforward given the extracellular nature of Aβ peptides. Nevertheless, these studies have not yet provided a clear picture of the predominant mechanism involved in the more restricted spread of Aβ pathology that may include intraneuronal, extraneuronal, and perivascular routes.…”
Section: Similarities and Differences In Pathological And Experimentamentioning
confidence: 99%
See 1 more Smart Citation
“…Si les concepts mécanistiques et infectieux sont bien associés dans le cas des maladies à prions, il semble clair que cela ne vaut pas dans tout phénomène biologique où ces modifications conformationnelles sont observées. Cette dernière décennie, un ensemble cohérent de données suggère que les assemblages de protéines mal conformées impliquées dans nombre de maladies neurodégénératives puissent se comporter comme des prions dans différentes modalités expérimentales (pour revue voir (Goedert, 2015) et (Walker & Jucker, 2015)) faisant naitre un certain nombre de néologismes tel que « prion-like », « prionoids », « propagons » ou encore « pseudoprions » pour qualifier ces structures moléculaires et leur comportement (Aguzzi, 2009;Ayers et al, 2016;Eisele & Duyckaerts, 2016). Ceci reflète la difficulté, en pathologie humaine, à utiliser le terme de prion qui fait implicitement craindre la possibilité d'une transmission interhumaine de certaines maladies neurodégénératives.…”
Section: Résuméunclassified
“…Multiple other proteins associated with neurodegenerative diseases, including amyloid-β peptide (Aβ), α-synuclein, mutant SOD1, mutant huntingtin and TDP-43, have also been shown to propagate protein misfolding pathology between cells in a similar prionlike manner, although the respective neuropathological cascades may vary in the human brain (reviewed in 9,10 ). How the accumulation and spreading of Aβ and Tau aggregates are mechanistically connected in human AD brain remains largely a mystery 11 . Clearly, however, Tau pathology can develop and spread in the absence of Aβ plaques, as evidenced by numerous tauopathies, such as familial cases of frontotemporal dementia that are primarily driven by aggregation-promoting mutations in the MAPT gene (that encodes the Tau protein) 12 .…”
Section: Cell-to-cell Propagation Of Tau In Alzheimer's Disease and Omentioning
confidence: 99%